Preparation method of polytetrafluoroethylene monofilament and high-wear-resistance polytetrafluoroethylene monofilament

By combining modified nano-alumina and polyether ether ketone with ultraviolet irradiation grafting technology, the problem of balancing wear resistance and friction coefficient of polytetrafluoroethylene monofilament was solved, achieving a high wear resistance and low friction effect.

CN121407248APending Publication Date: 2026-01-27NANTONG NTEC MONOFILAMENT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511800923.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-02
Publication Date
2026-01-27

AI Technical Summary

Technical Problem

Existing technologies struggle to improve the wear resistance of polytetrafluoroethylene (PTFE) monofilaments while maintaining a low coefficient of friction, and single-material filling cannot achieve both.

Method used

Polytetrafluoroethylene (PTFE) was modified using nano-alumina and polyether ether ketone (PEEK). Hard nano-alumina particles enhanced wear resistance, while soft PEEK inhibited inter-chain slippage. Ultraviolet irradiation grafting technology was combined to improve compatibility.

Benefits of technology

It significantly improves the wear resistance of PTFE monofilaments while maintaining a low coefficient of friction and enhancing mechanical and thermodynamic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121407248A_ABST
    Figure CN121407248A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: preparing modified polytetrafluoroethylene resin and modified nano aluminum oxide, and uniformly mixing the following components in parts by weight; 60-80 parts of modified polytetrafluoroethylene resin, 1-5 parts of modified nano aluminum oxide, 5-10 parts of polyether-ether-ketone and 10-30 parts of an extrusion aid are pre-pressed into a blank rod, the blank rod is put into an extruder to extrude protofilaments, the protofilaments enter a drying oven through a guide roller, the extrusion aid is removed, and the modified polytetrafluoroethylene resin is obtained. And sintering, stretching and shaping to form the high-wear-resistance polytetrafluoroethylene monofilament. Hard nanometer aluminum oxide particles and soft polyether-ether-ketone are adopted to modify polytetrafluoroethylene, so that the frictional wear performance of the polytetrafluoroethylene monofilament is enhanced synergistically.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention generally relates to the field of monofilaments, and more particularly to a method for preparing polytetrafluoroethylene (PTFE) monofilaments and high abrasion-resistant PTFE monofilaments. Background Technology

[0002] Polytetrafluoroethylene (PTFE) is a thermoplastic material polymerized from tetrafluoroethylene monomers. Its molecules have a linear structure, are unbranched, and exhibit high overall symmetry. PTFE possesses excellent lubricity, extremely low surface energy, and superior resistance to high and low temperatures and chemical corrosion. It has wide applications in plastics, coatings, textiles, and medical devices. Furthermore, PTFE is an excellent lubricant, with a dry friction coefficient as low as 0.1, making it the solid material with the lowest known coefficient of friction. However, due to the plate-like structure of PTFE's crystalline regions and the van der Waals forces connecting the molecular chains, the crystal plates are prone to sliding, resulting in an extremely high wear rate.

[0003] The tribological properties of PTFE can be significantly improved by filling it with nanoparticles or high-performance polymers such as polyetheretherketone, polyimide, and polyphenylene sulfide. However, filling with a single material often fails to simultaneously achieve low friction and high wear resistance. Therefore, how to improve the wear resistance of monofilaments while maintaining a low coefficient of friction is one of the important research topics in the field of polymer tribology. Summary of the Invention

[0004] In view of the above-mentioned defects or deficiencies in the prior art, it is desirable to provide a method for preparing polytetrafluoroethylene monofilament and a high wear-resistant polytetrafluoroethylene monofilament.

[0005] In a first aspect, a method for preparing polytetrafluoroethylene monofilament is provided, the method comprising: Preparation of modified polytetrafluoroethylene resin and modified nano-alumina, Mix the following components thoroughly according to their weight proportions, and allow them to stand and mature at the set temperature: 60-80 parts of the modified polytetrafluoroethylene resin The modified nano-alumina, 1-5 parts, 5-10 parts of polyetheretherketone 10-30 parts of extrusion aid The matured raw material is pre-pressed into a billet, and the billet is placed in an extruder to extrude the filament. The raw filament enters the drying oven via guide rollers to remove the extrusion aid, and is then sintered, stretched, and shaped to form a highly wear-resistant polytetrafluoroethylene monofilament.

[0006] As one possible approach, the "preparation of modified polytetrafluoroethylene resin" includes the following steps: The polytetrafluoroethylene powder was immersed in acetone and ultrasonically cleaned. After removal, it was air-dried for later use. Dimethylaminoethyl methacrylate and dimethylformamide were prepared into a solution and added to dried polytetrafluoroethylene powder. After mixing evenly, the mixture was placed under a high-pressure mercury lamp for illumination. The modified polytetrafluoroethylene powder was removed and immersed in deionized water for ultrasonic cleaning, followed by rinsing with ethanol and drying.

[0007] As an example, the solution concentration is 20-40 wt%, and the solid-liquid ratio of the solution to the polytetrafluoroethylene powder is 1 g: 10 ml.

[0008] As a feasible method, the high-pressure mercury lamp is illuminated under ultraviolet light, with an ultraviolet light intensity of 8000-20000 μm / cm. 2 The illumination time is 5-30 minutes.

[0009] As an example, the polytetrafluoroethylene powder is a dispersed resin with an average particle size of 400-600 μm.

[0010] As one possible approach, the "preparation of modified nano-alumina" includes the following steps: Nano-alumina was added to H2O2 and mixed evenly. The mixture was filtered and washed with ethanol to obtain powder. The powder was dried under vacuum to obtain hydroxylated nano-alumina powder. The hydroxylated nano-alumina powder was placed in ethanol and mixed evenly, and a certain mass of polyvinylpyrrolidone was added and mixed evenly. The mixture was then refluxed and stirred at a set temperature to carry out the reaction. The reaction mixture was washed with ethanol by filtration, and the resulting powder was dried under vacuum to obtain modified nano-alumina.

[0011] As an example, the mass ratio of the nano-alumina to the H2O2 is 1:10-1:50 g / ml; and the amount of the polyvinylpyrrolidone is 2-10 wt%.

[0012] As an achievable method, the polyetheretherketone is a powder with an average particle size of less than 75 μm, and the nano-alumina is in the α-crystal form with an average particle size of less than 50 μm.

[0013] As an feasible method, the pre-compression pressure is 5-10 MPa and the pre-compression speed is 50-100 mm / min; The extrusion pressure is 30-50 MPa, the extrusion speed is 25-50 mm / min, and the extrusion temperature is 50-80℃.

[0014] Secondly, a high wear-resistant polytetrafluoroethylene monofilament is provided, which is prepared by the above-mentioned method for preparing polytetrafluoroethylene monofilament.

[0015] According to the technical solution provided in the embodiments of this application, polytetrafluoroethylene (PTFE) is modified using hard nano-alumina particles and soft polyetheretherketone (PEEK) to synergistically enhance the tribological properties of PTFE monofilaments. Firstly, modified nano-alumina is added as a hard filler, which preferentially bears the load, and the surface of the nano-alumina can adsorb macromolecular chains, causing the macromolecular chains to entangle with each other, thereby preventing large-area damage to the PTFE band structure and improving the wear resistance of the PTFE monofilaments. Simultaneously, the hard nanoparticles can embed into the paired friction surfaces, thus mechanically anchoring the transfer film, enhancing the adhesion strength of the transfer film, and improving the mechanical and thermodynamic properties of the PTFE monofilaments. Secondly, the soft PEEK can effectively inhibit interlayer slippage between PTFE molecular chains and simultaneously encapsulate the hard nano-alumina particles, reducing the scratching damage to the transfer film caused by hard wear debris. Attached Figure Description

[0016] Other features, objects, and advantages of this application will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings: Figure 1 This is a flowchart of the polytetrafluoroethylene monofilament preparation method in this embodiment. Detailed Implementation

[0017] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, only the parts relevant to the invention are shown in the accompanying drawings.

[0018] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.

[0019] Please refer to Figure 1 This embodiment provides a method for preparing polytetrafluoroethylene monofilament, including: Preparation of modified polytetrafluoroethylene resin and modified nano-alumina, Mix the following components thoroughly according to their weight proportions, and allow them to stand and mature at the set temperature: 60-80 parts of the modified polytetrafluoroethylene resin The modified nano-alumina, 1-5 parts, 5-10 parts of polyetheretherketone 10-30 parts of extrusion aid The matured raw material is pre-pressed into a billet, and the billet is placed in an extruder to extrude the filament. The raw filament enters the drying oven via guide rollers to remove the extrusion aid, and is then sintered, stretched, and shaped to form a highly wear-resistant polytetrafluoroethylene monofilament.

[0020] This embodiment modifies polytetrafluoroethylene (PTFE) using hard nano-alumina particles and soft polyetheretherketone (PEEK) to synergistically enhance the tribological properties of PTFE monofilaments. First, modified nano-alumina is added as a hard filler, which preferentially bears the load, and the surface of the nano-alumina can adsorb macromolecular chains, causing them to entangle and preventing large-area damage to the PTFE banded structure, thus improving the wear resistance of the PTFE monofilaments. Simultaneously, the hard nanoparticles can embed into the paired friction surfaces, thus mechanically anchoring the transfer film, enhancing its adhesion strength, and improving the mechanical and thermodynamic properties of the PTFE monofilaments. Second, the soft PEEK effectively inhibits interlayer slippage between PTFE molecular chains and encapsulates the hard nano-alumina particles, reducing the scratching damage to the transfer film caused by hard abrasive particles.

[0021] The aforementioned polytetrafluoroethylene is a modified resin, specifically implemented through the following steps: The polytetrafluoroethylene powder was immersed in acetone and ultrasonically cleaned. After removal, it was air-dried for later use. Dimethylaminoethyl methacrylate and dimethylformamide were prepared into a solution and added to dried polytetrafluoroethylene powder. After mixing evenly, the mixture was placed under a high-pressure mercury lamp for illumination. The modified polytetrafluoroethylene powder was removed and immersed in deionized water for ultrasonic cleaning, followed by rinsing with ethanol and drying.

[0022] The concentration of the prepared solution is 20-40 wt%, and the solid-liquid ratio of the solution to the polytetrafluoroethylene powder is 1 g: 10 ml.

[0023] Optionally, the high-pressure mercury lamp illumination is ultraviolet light, and the ultraviolet light intensity is 8000-20000 μm / cm. 2 The illumination time is 5-30 minutes. In this embodiment, the grafted polytetrafluoroethylene is grafted using ultraviolet light irradiation, which is simple to operate, does not damage the material's properties, and has good durability.

[0024] The polytetrafluoroethylene used in this embodiment is a dispersion resin with an average particle size of 400-600 micrometers.

[0025] Compared to the traditional double helix chain of polytetrafluoroethylene (PTFE), the modified PTFE resin prepared in the above embodiments has side branches grafted onto the main chain, which enhances the degree of polymerization between molecular chains. At the same time, the dimethylaminoethyl methacrylate grafted onto PTFE improves the adhesion of PTFE itself and increases the compatibility between polyether ether ketone (PEEK) and modified PTFE in the subsequent monofilament preparation process, thereby significantly improving the wear resistance of the monofilament.

[0026] Using rigid nano-alumina particles as a filler, these nanomaterials can adsorb macromolecular chains on their surface, causing the macromolecular chains to entangle and preventing large-area damage to the polytetrafluoroethylene (PTFE) ribbon structure, thus improving the wear resistance of PTFE monofilaments. Simultaneously, these nano-alumina particles, being rigid fillers, act as load-bearing elements, preferentially supporting the load on the monofilaments. The nano-alumina particles are grafted with polyvinylpyrrolidone (PVP), and the specific steps include: Nano-alumina was added to H2O2 and mixed evenly. The mixture was filtered and washed with ethanol to obtain powder. The powder was dried under vacuum to obtain hydroxylated nano-alumina powder. The hydroxylated nano-alumina powder was placed in ethanol and mixed evenly, and a certain mass of polyvinylpyrrolidone was added and mixed evenly. The mixture was then refluxed and stirred at a set temperature to carry out the reaction. The reaction mixture was washed with ethanol by filtration, and the resulting powder was dried under vacuum to obtain modified nano-alumina.

[0027] Polyvinylpyrrolidone is a high molecular weight surfactant. When grafted onto alumina, it can form a nano-coating layer, which improves the interfacial compatibility between the matrix and the filler and the dispersibility of the filler. In addition, polyvinylpyrrolidone contains carbonyl groups, which can form hydrogen bonds with the hydroxyl groups on the surface of alumina, thereby improving the interfacial forces.

[0028] In this embodiment, polyvinylpyrrolidone is used as a modifier. It is a high molecular surfactant. When grafted onto alumina, it can form a nano-coating layer, which can improve the interfacial compatibility between the matrix and the filler and the dispersibility of the filler. Moreover, the modifier contains carbonyl groups, which can form hydrogen bonds with the hydroxyl groups on the surface of alumina to improve the interfacial forces.

[0029] The mass ratio of the nano-alumina to the H2O2 is 1:10-1:50 g / ml; the amount of polyvinylpyrrolidone used is 2-10 wt%, and the polyvinylpyrrolidone accounts for 2%-10% of the total mass of the system. The nano-alumina used is α-crystalline with an average particle size of less than 50 μm.

[0030] Subsequently, the modified polytetrafluoroethylene resin, modified nano-alumina, polyetheretherketone (PEEK), and extrusion aid are mixed in the specified weight proportions. Preferably, the first three materials are premixed, and then the extrusion aid is added for secondary mixing to ensure uniform mixing of the raw materials. In this embodiment, the PEEK used is a powder with an average particle size of less than 75 micrometers. The mixed raw materials are allowed to stand and mature at 30-40°C for 24-48 hours. Then, the matured raw materials are pre-pressed into rods, and the rods are extruded to form filaments. Optionally, the pre-pressing pressure is 5-10 MPa, and the pre-pressing speed is 50-100 mm / min. The extrusion pressure is 30-50 MPa, the extrusion speed is 25-50 mm / min, and the extrusion temperature is 50-80℃.

[0031] The extruded filaments are guided by rollers into an oven to remove the extrusion aid, then sintered and stretched, and finally shaped and wound. The stretching process uses a two-stage stretching method, with a selectable first-stage stretching temperature of 250-280℃ and a stretching ratio of 2-10 times, and a second-stage stretching temperature of 280-310℃ with a stretching ratio of 2-10 times. The heat-setting temperature is 320-330℃. In this embodiment, polytetrafluoroethylene (PTFE) is modified by filling with modified nano-alumina and polyetheretherketone (PEEK). The synergistic effect of the soft and hard fillers improves the wear resistance of the PTFE monofilaments while ensuring a low coefficient of friction. Ultraviolet irradiation grafting is used during the preparation process to improve the compatibility between the PTFE and the modified filler.

[0032] This embodiment also provides a high wear-resistant polytetrafluoroethylene monofilament, which is prepared by the above-described method for preparing polytetrafluoroethylene monofilament.

[0033] Several embodiments and comparative examples are given below: Example 1: S1: Preparation of modified polytetrafluoroethylene: (1) The polytetrafluoroethylene (PTFE) powder was soaked in acetone and ultrasonically cleaned for 30 minutes. After that, it was taken out and dried at room temperature for later use.

[0034] (2) Weigh dimethylaminoethyl methacrylate (DMAEMA) and dimethylformamide (DMF) to prepare a 20wt% solution. Add the solution to PTFE and mix thoroughly. Place it under a 500W high-pressure mercury lamp (with a wavelength of 254nm as the standard) with a light intensity of 10000μm / cm. 2 Irradiate for 20 minutes.

[0035] (3) Immerse the modified PTFE powder in deionized water, ultrasonically clean for 30 min, rinse with ethanol, and air dry at room temperature to obtain the modified PTFE.

[0036] S2: Preparation of modified nano-Al2O3: (1) Add nano-Al2O3 to H2O2 at a mass ratio of 1:20 (g / mL) and sonicate while stirring to make it evenly mixed. After sonication for 60 min, filter and wash the mixture several times with ethanol. Place the obtained powder in a vacuum drying oven and dry it overnight at 80℃ to finally obtain hydroxylated nano-Al2O3 powder.

[0037] (2) Weigh hydroxylated nano-Al2O3 into ethanol, sonicate for 30 min to disperse it evenly, then add 8 wt% polyvinylpyrrolidone to the above mixed solution, mix evenly, and reflux at 80℃ for 6 h. After the reaction is complete, filter and wash the mixture several times with ethanol, and place the obtained powder in a vacuum drying oven to dry overnight at 80℃ to finally obtain modified nano-Al2O3 powder.

[0038] S3: Preparation of high abrasion-resistant polytetrafluoroethylene monofilament: (1) Premix 80 parts of modified polytetrafluoroethylene powder, 5 parts of modified nano Al2O3 powder, and 5 parts of polyether ether ketone powder, and then add 10 parts of aviation kerosene for secondary mixing to ensure that the raw materials are mixed evenly. (2) Let the mixed raw materials stand at 30°C for 24 hours to mature; (3) The matured raw material is pre-pressed into a billet. The pre-pressing pressure is 10 MPa and the pre-pressing speed is 50 mm / min. (4) The pre-pressed billet is fed into the plunger cavity of the plunger extruder and the raw filament is extruded by pushing. The extrusion pressure is 50MPa, the extrusion speed is 50mm / min, and the extrusion temperature is 50℃. (5) The raw yarn enters the oven through the guide roller to remove the extrusion aid. The degreasing temperature is 200℃. Then it is sintered and stretched. The sintering temperature is 380℃. The stretching adopts two-stage stretching. The first-stage stretching temperature is 280℃ with a stretching ratio of 5 times. The second-stage stretching temperature is 310℃ with a stretching ratio of 8 times. Finally, it is shaped and wound at 320℃.

[0039] Example 2: The only difference was that the concentration of the dimethylformamide solution of dimethylaminoethyl methacrylate was changed to 40 wt%, and the rest was the same as in Example 1.

[0040] Example 3: Only the ultraviolet light intensity was changed to 15000 μm / cm 2 The rest is the same as in Example 1.

[0041] Example 4: The only change was to change the ultraviolet light irradiation time to 30 minutes; the rest was the same as in Example 1.

[0042] Example 5: S1: Preparation of modified polytetrafluoroethylene: (1) Soak the PTFE powder in acetone and perform ultrasonic cleaning for 30 minutes. After cleaning, remove it and let it air dry at room temperature for later use.

[0043] (2) Weigh DMAEMA and DMF to prepare a 40wt% solution. Add the solution to PTFE and mix thoroughly. Place it in a 500W high-pressure mercury lamp (with a wavelength of 254nm as the standard) with a light intensity of 10000μm / cm. 2 Irradiate for 20 minutes.

[0044] (3) Immerse the modified PTFE powder in deionized water, ultrasonically clean for 30 min, rinse with ethanol, and air dry at room temperature to obtain the modified PTFE.

[0045] S2: Preparation of modified nano-Al2O3: (1) Add nano-Al2O3 to H2O2 at a mass ratio of 1:20 (g / mL) and sonicate while stirring to make it evenly mixed. After sonication for 60 min, filter and wash the mixture several times with ethanol. Place the obtained powder in a vacuum drying oven and dry it overnight at 80℃ to finally obtain hydroxylated nano-Al2O3 powder.

[0046] (2) Weigh hydroxylated nano-Al2O3 into ethanol and sonicate for 30 min to disperse it evenly. Then add 8 wt% polyvinylpyrrolidone to the above mixed solution, mix evenly, and reflux at 80℃ for 6 h. After the reaction is complete, filter and wash the mixture several times with ethanol. Place the obtained powder in a vacuum drying oven and dry it overnight at 80℃ to finally obtain modified nano-Al2O3 powder.

[0047] S3: Preparation of high abrasion-resistant polytetrafluoroethylene monofilament: (1) Premix 83 parts of modified polytetrafluoroethylene powder, 2 parts of modified nano Al2O3 powder, and 5 parts of polyether ether ketone powder, and then add 10 parts of aviation kerosene for secondary mixing to ensure that the raw materials are mixed evenly. (2) Let the mixed raw materials stand at 30°C for 24 hours to mature; (3) The matured raw material is pre-pressed into a billet. The pre-pressing pressure is 10 MPa and the pre-pressing speed is 50 mm / min. (4) The pre-pressed billet is fed into the plunger cavity of the plunger extruder and the raw filament is extruded by pushing. The extrusion pressure is 50MPa, the extrusion speed is 50mm / min, and the extrusion temperature is 50℃. (5) The raw yarn enters the oven through the guide roller to remove the extrusion aid. The degreasing temperature is 200℃. Then it is sintered and stretched. The sintering temperature is 380℃. The stretching adopts two-stage stretching. The first-stage stretching temperature is 280℃ with a stretching ratio of 5 times. The second-stage stretching temperature is 310℃ with a stretching ratio of 8 times. Finally, it is shaped and wound at 320℃.

[0048] Example 6: The only change was to the material ratio of 75 parts modified polytetrafluoroethylene powder, 5 parts modified nano Al2O3 powder, 10 parts polyether ether ketone powder, and 10 parts aviation kerosene, with the rest being the same as in Example 5.

[0049] Comparative Example 1: PTFE monofilaments were prepared by mixing 90 parts of unmodified polytetrafluoroethylene powder and 10 parts of aviation kerosene according to step S3 in Example 1.

[0050] Comparative Example 2: Take 80 parts of unmodified polytetrafluoroethylene powder, 5 parts of modified nano-Al2O3 powder, 5 parts of polyetheretherketone powder, and 10 parts of aviation kerosene. The modified nano-alumina powder is prepared according to S2 in Example 1, and the monofilaments are prepared according to S3 in Example 1.

[0051] Comparative Example 3: Take 80 parts of unmodified polytetrafluoroethylene powder, 5 parts of modified nano-Al2O3 powder, and 15 parts of aviation kerosene. The modified nano-alumina powder is prepared according to S2 in Example 1, and the monofilament is prepared according to S3 in Example 1.

[0052] Comparative Example 4: Take 80 parts of unmodified polytetrafluoroethylene powder, 10 parts of polyetheretherketone powder, and 10 parts of aviation kerosene, and prepare PTFE monofilaments according to step S3 in Example 1.

[0053] The abrasion resistance of the monofilaments prepared in the above embodiments and comparative examples was tested using a reciprocating friction tester with a friction speed of 60 times / min, a friction cycle of 5000 times, and a load of 1 kg. The strength of the monofilaments before and after wear was tested, and the strength retention rate was calculated. The test coefficients are shown in the table below.

[0054] Referring to Examples 1 to 6 in the table above, the polytetrafluoroethylene monofilaments prepared by this invention, through the addition of modified nano-alumina and polyetheretherketone, significantly improve the wear resistance of the monofilaments, while the original low coefficient of friction of the monofilaments remains unaffected and is even reduced accordingly. Furthermore, the addition of fillers does not affect the strength of the monofilaments themselves, and even improves it to some extent.

[0055] In the comparative examples above, the addition of modified nano-alumina or polyetheretherketone, or the use of polytetrafluoroethylene (PTFE) to prepare monofilaments (as in Comparative Example 1), resulted in low wear resistance and a high coefficient of friction for the monofilaments. Furthermore, the addition of modified nano-alumina in Comparative Example 3 improved the wear resistance of the monofilaments, but did not significantly enhance their strength.

[0056] In summary, this embodiment improves the wear resistance of polytetrafluoroethylene monofilaments by grafting polytetrafluoroethylene resin with ultraviolet light irradiation and by modifying polytetrafluoroethylene with modified nano-alumina and polyether ether ketone. The synergistic effect of soft and hard fillers improves the wear resistance of polytetrafluoroethylene monofilaments while maintaining their low coefficient of friction.

[0057] It should be understood that the terms "center," "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer" used above to indicate orientation or positional relationships are based on the orientation or positional relationships shown in the accompanying drawings and are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of the invention; the directional terms "inner" and "outer" refer to the inside or outside relative to the outline of each component itself. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature.

[0058] The above description is merely a preferred embodiment of this application and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this application is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above features with (but not limited to) technical features with similar functions disclosed in this application.

Claims

1. A method for preparing polytetrafluoroethylene monofilament, characterized in that, The method includes: Preparation of modified polytetrafluoroethylene resin and modified nano-alumina, Mix the following components thoroughly according to their weight proportions, and allow them to stand and mature at the set temperature: 60-80 parts of the modified polytetrafluoroethylene resin The modified nano-alumina, 1-5 parts, 5-10 parts of polyetheretherketone 10-30 parts of extrusion aid The matured raw material is pre-pressed into a billet, and the billet is placed in an extruder to extrude the filament. The raw filament enters the drying oven via guide rollers to remove the extrusion aid, and is then sintered, stretched, and shaped to form a highly wear-resistant polytetrafluoroethylene monofilament.

2. The method for preparing polytetrafluoroethylene monofilament according to claim 1, characterized in that, The "preparation of modified polytetrafluoroethylene resin" includes the following steps: The polytetrafluoroethylene powder was immersed in acetone and ultrasonically cleaned. After removal, it was air-dried for later use. Dimethylaminoethyl methacrylate and dimethylformamide were prepared into a solution and added to dried polytetrafluoroethylene powder. After mixing evenly, the mixture was placed under a high-pressure mercury lamp for illumination. Remove the modified polytetrafluoroethylene powder and immerse it in deionized water for ultrasonic cleaning, followed by rinsing with ethanol and drying.

3. The method for preparing polytetrafluoroethylene monofilament according to claim 2, characterized in that, The solution concentration is 20-40 wt%, and the solid-liquid ratio of the solution to the polytetrafluoroethylene powder is 1 g: 10 ml.

4. The method for preparing polytetrafluoroethylene monofilament according to claim 2, characterized in that, The high-pressure mercury lamp is illuminated under ultraviolet light, with an intensity of 8000-20000 μm / cm. 2 The illumination time is 5-30 minutes.

5. The method for preparing polytetrafluoroethylene monofilament according to claim 2, characterized in that, The polytetrafluoroethylene powder is a dispersion resin with an average particle size of 400-600 μm.

6. The method for preparing polytetrafluoroethylene monofilament according to claim 1, characterized in that, The "preparation of modified nano-alumina" includes the following steps: Nano-alumina was added to H2O2 and mixed evenly. The mixture was filtered and washed with ethanol to obtain powder. The powder was dried under vacuum to obtain hydroxylated nano-alumina powder. The hydroxylated nano-alumina powder was placed in ethanol and mixed evenly, and a certain mass of polyvinylpyrrolidone was added and mixed evenly. The mixture was then refluxed and stirred at a set temperature to carry out the reaction. The reaction mixture was washed with ethanol by filtration, and the resulting powder was dried under vacuum to obtain modified nano-alumina.

7. The method for preparing polytetrafluoroethylene monofilament according to claim 6, characterized in that, The mass ratio of the nano-alumina to the H2O2 is 1:10-1:50 g / ml; the amount of the polyvinylpyrrolidone is 2-10 wt%.

8. The method for preparing polytetrafluoroethylene monofilament according to claim 6, characterized in that, The polyetheretherketone is a powder with an average particle size of less than 75 μm, and the nano-alumina is in the α-crystal form with an average particle size of less than 50 μm.

9. The method for preparing polytetrafluoroethylene monofilament according to claim 1, characterized in that, The pre-compression pressure is 5-10 MPa, and the pre-compression speed is 50-100 mm / min; The extrusion pressure is 30-50 MPa, the extrusion speed is 25-50 mm / min, and the extrusion temperature is 50-80℃.

10. A highly wear-resistant polytetrafluoroethylene monofilament, characterized in that, It is prepared by the method for preparing polytetrafluoroethylene monofilament according to any one of claims 1-9.